Avaliação de misturas asfálticas recicladas mornas com uso de ligantes convencional e modificado por polímero - Bohn, Kátia Aline (2017)
The growing concern with the environment, in recent years, awakens the study of new technologies in the field of paving. Less polluting technologies that minimize the degradation of the environment and that seek to meet sustainability measures are the guiding principle of many researches currently developed. Within this context, pavement recycling emerged as an alternative to reduce the amount of virgin aggregates needed in new pavements, and to reuse this material of great economic value, which was previously deposited on the environment, without adequate reuse. In order to meet the requirements of the Kyoto Protocol of 1997, warm asphalt mixtures have emerged, which have brought a number of benefits when compared to conventional hot mixes, allowing the reduction of the machining and compacting temperatures usually employed, as well as the reduction of consumption decreasing the emission of pollutants and improving the working conditions of operators. Thus, the study of the warm recycled asphalt mixtures begins, which combine the insertion of the recycled pavement material with the technology of the warm mixtures, obtaining an expressive gain in the amount of material to be inserted in new asphalt masses, due to the lower reheating of the milled material. The aim of the present study was to conduct a study on warm recycled asphalt mixtures using conventional binders CAP 50/70 and modified by polymer CAP 60/85. Four asphalt mixtures were studied per binder, between conventional hot mix (reference), warm (no milling), and warm mixtures with 25 and 50% milling (replacing the total mass of virgin aggregates), totaling in eight blends surveyed. After being dosed by the Superpave methodology and analyzed for its volumetric and densification properties, the samples were evaluated for tensile strength (tensile strength by diametral compression and Flow Number), deformability (modulus of resilience and complex modulus) and adhesion and cohesion (Lottman Modified and wear resistance). The main results indicated that the performance of the warm asphalt mixtures is equivalent to the conventional hot mixes. There is also a significant improvement for blends with embedded milling, highlighting the gains obtained in the Flow Number test, which grows significantly as the milling content of the blend increases, as well as the results of adhesion and cohesion through Modified Lottman test, which proved to be positive, probably due to the milling used in the present research to have modified polymer binder (CAP 60/85) in its composition. As for the modified binder mixtures, it is possible to affirm that there is an expressive improvement of performance when compared to the mixtures with conventional binder.